"I don't like hearing Angel and not seeing her! Why did we do that?" An Exploration of Students' Media Literacy Development Through Production - Michele Luchs; Winston Emery (The Canadian Network for Innovation in Education (CNIE), 2004)
Abstract: In this exploratory casestudy we look at student media production to find out what students know and have learned about the media through production work. We used a media education conceptual framework developed by Dick as a means of describing the day to day media learning of a group of ten students, four girls and six boys, producing a video documentary on rape. We found that as they worked, the students encountered most of the concepts of Dick's framework; however, with the exception of the development of a sophisticated understanding of the documentary genre, there was little formal opportunity for the students to articulate their nascent critical consciousness about the media.